PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, LEVERAGE, RETURN ON ASSETS DAN KOMISARIS INDEPENDEN TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL (PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016) - MULYADI MULYADI; SISKA ARIYANTI (Universitas Muhammadiyah Tangerang, 2018)
The purpose of this research is to know the effect of firm size, age of company, leverage, return on assets and commissioner independent partially and together at Manufacturing companylisted on the Indonesia Stock Exchange (IDX). The research period used is 4 years the period 2013-2016. The study population includes all Manufacturing companies listed on Indonesia Stock Exchange period 2013-2016. Technique of Sampling by using technique of purposive sampling. Based on the predetermined criteria a sample of 20 companies was obtained. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. method of data analysis used regression analysis of panel data. The results of this study indicate that return on assets affect the diosclosure of of intellectual capital, while firm size, age of company, leverage, and independent commissioner have no effect on intellectual capital disclosure. Keywords: Firm Size, Age of Company, Leverage, Return On Assets, Independent Commissioner, Intellectual Capital Disclosure